2020
DOI: 10.1149/2162-8777/abb799
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of SiO2NPs/MWCNTs Nanocomposite and Effect on the Properties of Na-Bentonite Water Based Drilling Fluids: Experimental Investigation

Abstract: Drilling fluid is an essential element of the drilling operations and has many functions. Some of these are wellbore cleaning, checking high formation pressures and corrosion protection, etc. This study aimed to determine the effects of multi-walled carbon nanotubes containing silisyum dioxide nanoparticles (SiO 2 NPsMWCNTs) were investigated on the rheological and filtration loss properties of Na-Bentonite water based drilling fluids (Na-WBDF).In this context SiO 2 NPs/MWCNTs was produced by chemical vapor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…According the results of their study, water based drilling muds with TiO 2 NPs/MWCNTs addition is increased the plastic viscocity value 71.4%; apparent viscosity value 41.8%; yield point value of 28%; cake thickness value is 11%; the value of 10 s is 8.3%; value of 10 min by 5.6% and decreased the filtration loss by 8.6%. In their study where Özkan et al 29 added MWCNTs functionalized with SiO 2 NPs to water-based drilling mud; They found that with the increasing amount of SiO 2 NPs/MWCNTs, PV, AV, YP, 10 s, 10 min, cake thickness values increased by 71.4%, 51.9%, 44%, 25%, 33.3%, 11%, respectively. At the same time, they found that the filtration loss value decreased by 13.8%.…”
mentioning
confidence: 99%
“…According the results of their study, water based drilling muds with TiO 2 NPs/MWCNTs addition is increased the plastic viscocity value 71.4%; apparent viscosity value 41.8%; yield point value of 28%; cake thickness value is 11%; the value of 10 s is 8.3%; value of 10 min by 5.6% and decreased the filtration loss by 8.6%. In their study where Özkan et al 29 added MWCNTs functionalized with SiO 2 NPs to water-based drilling mud; They found that with the increasing amount of SiO 2 NPs/MWCNTs, PV, AV, YP, 10 s, 10 min, cake thickness values increased by 71.4%, 51.9%, 44%, 25%, 33.3%, 11%, respectively. At the same time, they found that the filtration loss value decreased by 13.8%.…”
mentioning
confidence: 99%